Tackling vulnerability to debt. Affordable lending alternatives and financial education: an evidence review. (26th October 2018) - Mosedale, Sarah; Simpson, Glenn; Popay, Jennie; McGill, Rory; Cooper, Paula; Taylor, Catherine; Fisher, Kate; Sant, Helen
Abstract : The pathways to vulnerability to debt and what works to reduce such vulnerability are poorly understood. To address this knowledge gap, we conducted an evidence review. Many low-income borrowers have little alternative but to resort to high interest lending. Developing 'affordable' lending alternatives has been a challenge. Policy-makers have advocated person-centred approaches (for example, financial education) despite little evidence supporting the efficacy of such behavioural measures. Arguably this has shifted the burden of social responsibility and risk for managing problem debt primarily onto borrowers. While better regulation of the credit industry is needed, ultimately policymakers need to look beyond market-based solutions.